Current Controversies around Carbohydrate Restriction and the Risk of High-Protein Diets - Shaw Watanabe (Diabetes Research, 2015)
Recently, a Low carbohydrate (LCH) diet has been recommended by many doctors to control hyperglycemia and overweight. Unlike a traditional calorie-restricted diet, a carbohydrate-restricted diet typically contains less than 15% of the total energy intake from carbohydrates and about 30% from proteins. High glycemic index carbohydrates are the only cause of the glucose spike, so the main benefit of a LCH diet is not to cause postprandial hyperglycemia, which is considered to be the most serious risk factor for arteriosclerosis in diabetic patients. Life With Diabetes1 says that all absorbable carbohydrate foods turn to glucose in the blood, while fats and proteins do not, at least directly. Compared to a calorie-restricted diet, a carbohydrate-restricted diet accelerates fat metabolism yielding to ketogenic energy and helps gluconeogenesis in the liver, resulting in a more effective control of weight.